Corn Marketing Development Strategy In Lima Puuh Kota Regency - Fajri Ramadhan; Filya Hidayati; Al Bastoni; Abdul Latif (Cita konsultindo, 2024)
The purpose of the study was to determine the Internal and External Factors of Maize Marketing Development and determine the development strategy of Maize Marketing. Maize is one of the main crop commodities in Indonesia that has a relatively wide range of uses, especially for human consumption and animal feed needs. This research uses descriptive research methods. This research was conducted in Lima Puluh Kota Regency. This research is located in Mungka Sub-district. The technique used in this research is nonprobability sampling technique, namely snowball sampling. the analysis that will be used is descriptive analysis, farming analysis, IFE and EFE analysis, SWOT analysis and strategic architecture design. The results showed that The strategy for developing maize marketing in Lima Puluh Kota Regency is the SO (Strengths-Opportunities) strategy, consisting of: (a) Increasing marketing cooperation with maize farmers, and (b) Increasing marketing cooperation with farmers.